A stalagmite δ18O record from Jinfo Cave, southern China reveals early-mid holocene variations in the East Asian Summer Monsoon. (30th January 2020) - Yang, Xunlin; Liu, Ruikai; Zhang, Rui; Wang, Baoyan; Zhang, Riping; Yan, Yingran
Abstract: The stability of the East Asian Summer Monsoon (EASM) during the early Holocene and the timing of the Holocene optimum have been intensely debated. Both stalagmite and lake records from northern China imply that there was a millennium-scale monsoon weakening event during the early Holocene, but whether this phenomenon is common across the Asian monsoon region remains unclear due to a paucity of records from southern China. We present results from U–Th dating and 433 stable carbon and oxygen isotope datapoints in order to investigate variations in the EASM during the early-mid Holocene in southern China. The results show that stalagmite δ 18 O values are relatively low in the period of 10.1–9.6 ka BP, indicating enhanced monsoon activity in the early Holocene. The stalagmite δ 18 O values for the period of 9.1–8.1 ka BP are characterized by a "w" type oscillation, indicating that there was a period of monsoon recession. In contrast, the period of 8.0–6.0 ka BP is characterized by relatively low, implying a strong monsoon. The results of our study indicate there was a millennial-scale weakening of the monsoon during the early Holocene in southern China. This suggests that the early Holocene monsoon weakening events are widespread throughout the monsoon region of eastern China.